Accident Analysis Work with Failure Mode and Effect Method Analysis at PT. Gansa Furindo Indonesia - Hasiholan Manurung; Algi Fahri; Humiras Hardi Purba; Hibarkah Kurnia (Universitas Ahmad Dahlan Indonesia, 2021)
PT. Gansa Furindo Indonesia (GFI) is a company engaged in painting and powder coating services established in 1990. In the process of making such a long and involving painting machine and labor, it does not cover the possibility of work accidents. There are 3 categories of work accidents: minor accidents, moderate accidents, and serious/major accidents. For the 3 crash categories, it is seen how severe the injuries suffered in the work accident. This study aims to determine the steps to prevent and repair work accidents after knowing the categories of work accidents that occur. This research is focused on the production department, especially in the machining area where work accidents occur due to the lack of employee awareness of Health Safety and Environment (HSE). Work accidents include crashing objects with a static state of 108 RPN, contact with the machine while moving when taking the material inside the machine is 196 RPN, short circuit of 160 RPN, reverse mounting of 90 RPN and less neat cutting in the iron cutting of 168 RPN. Therefore, improvements are made in preventing work accidents that occur by making the latest Standard Operational Procedure (SOP).